Standardizing Single-Frame Phase Singularity Identification Algorithms and Parameters in Phase Mapping During Human Atrial Fibrillation - Li, Xin; Almeida, Tiago P.; Dastagir, Nawshin; Guillem, María S.; Salinet, João; Chu, Gavin S.; Stafford, Peter J.; Schlindwein, Fernando S.; Ng, G. André (Frontiers in Physiology, 2020)
Purpose: Recent investigations failed to reproduce the positive rotor-guided ablation outcomes shown by initial studies for treating persistent atrial fibrillation (persAF). Phase singularity (PS) is an important feature for AF driver detection, but algorithms for automated PS identification differ. We aim to investigate the performance of four different techniques for automated PS detection. Methods: 2048-channel virtual electrogram (VEGM) and electrocardiogram signals were collected for 30 s from ten patients undergoing persAF ablation. QRST-subtraction was performed and VEGMs were processed using sinusoidal wavelet reconstruction. The phase was obtained using Hilbert transform. PSs were detected using four algorithms: 1) 2D image processing based and neighbour-indexing algorithm; 2) 3D neighbour-indexing algorithm; 3) 2D kernel convolutional algorithm estimating topological charge; 4) topological charge estimation on 3D mesh. PS annotations were compared using the structural similarity index (SSIM) and Pearson’s correlation coefficient (CORR). Optimized parameters to improve detection accuracy were found for all four algorithms using Fβ score and 10-fold cross-validation compared with manual annotation. Local clustering with density-based spatial clustering of applications with noise (DBSCAN) was proposed to improve algorithms 3 and 4. Results: The PS density maps created by each algorithm with default parameters were poorly correlated. Phase gradient threshold and search radius (or kernels) were shown to affect PS detections. The processing times for the algorithms were significantly different (p<0.0001). The Fβ scores for algorithms 1,2, 3, 3+DBSCAN, 4 and 4+DBSCAN were 0.547, 0.645, 0.742, 0.828, 0.656 and 0.831. Algorithm 4 + DBSCAN achieved the best classification performance with acceptable processing time (2.0 ± 0.3 s). Conclusion: AF driver identification is dependent on the PS detection algorithms and their parameters, which could explain some of the inconsistencies in rotor-guided ablation outcomes in different studies. For 3D triangulated meshes, algorithm 4+DBSCAN with optimal parameters was the best solution for real-time, automated PS detection due to accuracy and speed. Similarly, algorithm 3+DBSCAN with optimal parameters is preferred for uniform 2D meshes. Such algorithms – and parameters – should be preferred in future clinical studies for identifying AF drivers and minimising methodological heterogeneities. This would facilitate comparisons in rotor-guided ablation outcomes in future works.